Effect of thermal cycles on the engineering properties and durability of sustainable fibrous high-strength concrete - Hakeem, Ibrahim Y.; Hosen, MD. Akter; Alyami, Mana; Qaidi, Shaker; Özkılıç, Yasin O.; Alhamami, Ali; Alharthai, Mohammad (Frontiers in Materials, 2023)
In this research, the effect of heat–cool cycles (HCCs) on high-strength concrete (HSC) containing steel fibres (SFs), polypropylene fibres (PPFs), and date palm fibres (DPFs), which were named fibrous high-strength concrete (FHSC), was studied. To produce FHSC, three doses of 0.2, 0.6, and 1 percent of each fibre were used. All samples were tested after 28 days of normal water curing and 270 days of exposure to HCCs (continuing the authors’ project and research published at 28 and 180 days). This entails heating for 2 days at 60 C in the oven and cooling for another 2 days at room temperature for 270 days. The experiment’s findings revealed that fibre reinforcement in concrete enhances its strength and durability. By incorporating the three types of fibres into high-strength concrete, with and without HCCs, the modulus of rupture was significantly increased. In both conditions, including with or without the implementation of HCCs, incorporating the three fibre types into the HSC showed a significant increase in toughness. As a result, natural date palm fibres can produce sustainable FHSC that can withstand harsh environmental conditions. Moreover, compared to the previous study conducted by the authors at 180 days, there is a slight severity in both the pattern of decrease and increase of the studied characteristics at 270 days caused by the effect of thermal cycles and fibres.